The first atomistic modelling-aided reproduction of morphologically defective single walled carbon nanohorns - Furmaniak, S.; Terzyk, A.; Kaneko, K.; Gauden, P.; Kowalczyk, Piotr; Itoh, T. (R S C Publications, 2013)
A new modelling-aided approach for the atomistic model of single walled carbon nanohorn (SWNH) creation is presented, based on experimental evidence, on realistic potential of carbon–carbon interactions and on molecular simulations. A new model of SWNHs is next used to predict Ar adsorption properties and to check the molecular fundamentals of the adsorption mechanism. The influence of the apex angle value, nanohorn diameter and nanohorn length on the shapes of isotherms, enthalpy, high resolution as-plots and adsorption potential distribution curves is checked. Finally the comparison with new experimental Ar adsorption results is shown and the conclusions on the porosity of real SWNH aggregates are given.